Analisis Unit Cost pada Menu Makanan yang Disajikan dalam Penyelenggaraan Makanan di SD/SMP Islam Terpadu Al-Fahmi Kota Palu: Analysis Of Cost Units On The Food Service Menu Presented In The Food Service At SMPIT Al-Fahmi, Palu City - Nurjaya Nurjaya; Ketrin Ketrin; Irawati Irawati (Svasta Harena: Jurnal Ilmiah Gizi, 2020)
Unit cost calculation plays an important role in the effectiveness and efficiency of an organization's budget. The purpose of this research is to analyze the unit cost in the food menu served in the organization of food in the Al-Fahmi Integrated Islamic Elementary / Middle School in Palu City. This type of research used in this research is a quantitative study with descriptive approach with interview techniques and sample collection in this study is the entire menu of food served at SD / SMP IT Al-Fahmi, Palu City. The results showed that the implementation of food in SD / SMP IT Al-Fahmi Palu City is serving 1027 consumers, with 5 days menu cycle, there is a standard menu / recipe, and the prevailing food unit price is the market price. The available workforce is 24 people, aspects of labor costs consisting of salaries, incentive costs, transportation, and health benefits. Overhead costs consist of fixed costs with goods that use 3 years, 10 years and 15 years. Variable costs are consumables, electricity and fuel and depreciation. So that the obtained cost of food per person per day is Rp.9,661.83, -, labor costs per person per day is Rp.1,982.91, overhead costs per person per day is 265.73, -, unit cost at Rp.14,012.31 / person / days, and profit is Rp. 2,101.84, - / person / day. It is expected that the calculated unit cost can be considered in budget planning so that effectiveness and efficiency can be increased.